Major differences in dissolved organic matter characteristics and bacterial processing over an extensive brackish water gradient, the Baltic Sea - Rowe, Owen F. (2018)
Dissolved organic matter (DOM) in marine waters is a complex mixture of compounds and elements that contribute substantially to the global carbon cycle. The large reservoir of dissolved organic carbon (DOC) represents a vital resource for heterotrophic bacteria. Bacteria can utilise, produce, recycle and transform components of the DOM pool, and the physicochemical characteristics of this pool can directly influence bacterial activity; with consequences for nutrient cycling and primary productivity. In the present study we explored bacterial transformation of naturally occurring DOM across an extensive brackish water gradient in the Baltic Sea. Highest DOC utilisation (indicated by decreased DOC concentration) was recorded in the more saline southerly region where waters are characterised by more autochthonous DOM. These sites expressed the lowest bacterial growth efficiency (BGE), whereas in northerly regions, characterised by higher terrestrial and allochthonous DOM, the DOC utilisation was low and BGE was highest. Bacterial processing of the DOM pool in the south resulted in larger molecular weight compounds and compounds associated with secondary terrestrial humic matter being degraded, and a processed DOM pool that was more aromatic in nature and contributed more strongly to water colour; while the opposite was true in the north. Nutrient concentration and stoichiometry and DOM characteristics affected bacterial activity, including metabolic status (BGE), which influenced DOM transformations. Our study highlights dramatic differences in DOM characteristics and microbial carbon cycling in sub-basins of the Baltic Sea. These findings are critical for our understanding of carbon and nutrient biogeochemistry, particularly in light of climate change scenarios.